PENGARUH MODEL THE 4 Cs + C TERHADAP LOYALITAS NASABAH PERBANKAN SYARIAH DI DKI JAKARTA - Hendratmoko; Elisabeth Vita (Jurnal Manajemen, 2020)
Islamic financial inclusion which only reaches 9.1% in Indonesia. Existing customer loyalty should have a positive impact on increasing Islamic financial inclusion because satisfied and loyal customers will share their stories and even recommend them to others. This study aims to identify and analyze the factors that influence the loyalty of sharia banking customers through the approach of The 4 Cs + C model which is a development of The 4 Cs Model and Compliance. Variable Compliance is included because of this research concerns on Islamic banking. The research method used in this study is Quantitative research, with sampling based on the purposive random sampling method. Sampling is only collected in DKI Jakarta with the criteria of being a customer or having used sharia banking services for a minimum of three years. The number of samples taken was 122 respondents, and from the results of the study found that the variable Consumer and Compliance significantly influence the variable Loyalty. While the other three variables namely Cost, Communication and Convenience do not significantly influence the variable Loyalty. Keywords: Loyalty, Consumer needs and wants, Compliance